THE IMPACT OF CASH TURNOVER, ACCOUNTS RECEIVABLE TURNOVER, AND INVENTORY TURNOVER ON RETURN ON ASSETS (ROA) FOR AGRIBUSINESS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) DURING THE PERIOD 2016 - 2020 - Hasanudin Hasanudin; Dipa Teruna Awaloedin; Dea Dwi Arviany (SEAN Institute, 2022)
The purpose of this research is to assess the impact that cash turnover, accounts receivable turnover, and inventory turnover have on the return on assets (ROA) of agricultural firms that are traded on the Indonesia Stock Exchange (IDX) throughout the period of 2016-2020. For the purpose of this research, the sample consisted of twenty agricultural corporations that were listed on the Indonesia Stock Exchange between the years 2016 and 2020. Secondary data in the form of financial statements received from the Indonesia Stock Exchange are used for the purpose of this research. In this particular research endeavor, the kind of statistical analysis that was used was a linear regression analysis of panel data carried out using the eviews 9 software. The findings indicate that CTO has a positive impact on ROA that is not statistically significant, RTO has a positive effect on ROA that is statistically significant, and ITO has a negative effect on ROA that is statistically significant..